2010
DOI: 10.1017/s0007114510004836
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the catechol-O-methyltransferase genotype on the acute responsiveness of vascular reactivity to a green tea extract

Abstract: The beneficial effects of green tea catechins, such as the proposed improvement in endothelial function, may be influenced by phase II metabolism during and after absorption. The methylation enzyme, catechol-O-methyltransferase (COMT), has a missense mutation rs4680 (G to A), proposed to result in a 40 % reduction in enzyme activity. In the present pilot study, twenty subjects (ten of each homozygous COMT genotype) were recruited. Green tea extract capsules (836 mg green tea catechins) were given in a fasted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
(37 reference statements)
3
16
0
Order By: Relevance
“…The significance of an increased insulin response to a high-carbohydrate meal in participants with the G/G genotype taking GTE is unclear, although it could be indicative of the need to secrete additional insulin to manage blood glucose concentrations over time compared to individuals with other forms of the COMT genotype and those not taking GTE; yet, the sample size of this group was small, making it difficult to draw definitive conclusions. Our results are in agreement with those of another study (23) that reported finding greater post-prandial insulin concentrations after the consumption of GTE (836 mg catechins) in individuals with the G/G genotype compared to those with the G/A or A/A COMT genotypes. Similarly, Kring, et al (33) determined that there was an 11.6% increased frequency of the G/G COMT genotype in individuals with impaired glucose tolerance or type 2 diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The significance of an increased insulin response to a high-carbohydrate meal in participants with the G/G genotype taking GTE is unclear, although it could be indicative of the need to secrete additional insulin to manage blood glucose concentrations over time compared to individuals with other forms of the COMT genotype and those not taking GTE; yet, the sample size of this group was small, making it difficult to draw definitive conclusions. Our results are in agreement with those of another study (23) that reported finding greater post-prandial insulin concentrations after the consumption of GTE (836 mg catechins) in individuals with the G/G genotype compared to those with the G/A or A/A COMT genotypes. Similarly, Kring, et al (33) determined that there was an 11.6% increased frequency of the G/G COMT genotype in individuals with impaired glucose tolerance or type 2 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Insulin has also been associated with energy balance (18) , and several RCTs have demonstrated increased insulin sensitivity with the consumption of GTC (19)(20)(21) . However, few human studies examining the immediate post-prandial effects of GTC on these hormones have been conducted (22,23) . To date, the results are inconclusive, with one study finding no differences in the area under the curve (AUC) for glucose and insulin after meal consumption, although higher satiety was reported among participants (22) , whereas another single-arm study did not provide a control group to enable a comparison of the results (23) .…”
mentioning
confidence: 99%
“…In animals, concurrent effects on insulin resistance and vascular function have been reported [172]. To date one study has been published evaluating these parameters in humans, and found significant effect of green tea extract on post-meal blood pressure and insulin response, with interesting differences by catechol-O-methyl transferase (COMT) genotype [175]. The fact of shared mechanisms with insulin signaling in endothelium and promising pre-clinical data in animals suggests that green tea-based therapies may be of particular benefit in insulin resistance-associated vascular dysfunction, but this has not yet been rigorously assessed.…”
Section: Therapies That Target the Endotheliummentioning
confidence: 99%
“…Eight studies have reported the impact of genetic polymorphisms on the cardiometabolic health effects of green tea (57, 58), coffee or caffeine (5961), and plant sterols (6264) (Table 1). The beneficial effects of green tea catechins may be predisposed by polymorphisms in genes encoding phase II metabolism enzymes during and after the consumption.…”
Section: Determinants Of Interindividual Variability In Biomarkers Ofmentioning
confidence: 99%
“…The missense mutation rs4680 (G to A) in the COMT gene, coding for methylation enzyme, results in a 40% decrease in enzyme activity. In a pilot study performed by Miller et al (58), 20 subjects (10 homozygous COMT GG or 10 AA genotype) were given green tea extract capsules (836 mg green tea catechins) in a fasted state and with a high-carbohydrate breakfast. The modification in digital volume pulse (DVP) stiffness index from baseline was observed to be different between genotype groups at 120 and 240 min, with a lower stiffness index in the GG individuals.…”
Section: Determinants Of Interindividual Variability In Biomarkers Ofmentioning
confidence: 99%